The Astrophysics of Berossos the Chaldean - Toulmin, Stephen
A Radially Symmetric Reconstruction. A Laterally Symmetric Reconstruction. The Significance of Berossos’s Theory. Indirect Evidence of a “Rectangular” Cosmology.